Differential analysis of clinical outcomes in cerebral infarction associated with REM-OSA and NREM-OSA: a retrospective database study - Xu, Liwen; Yu, Wenyi; Sun, Shutong; Zheng, Yixi; Jing, Tianyu; Xu, Gang; Tang, Tieyu; Chu, Cheng (Frontiers in Neurology, 2025)
BackgroundObstructive sleep apnea (OSA) is one of the factors that affect the prognosis of cerebral infarction. Rapid eye movement-related obstructive sleep apnea (REM-OSA) has been confirmed as an important clinical subtype of OSA, yet it is frequently overlooked in clinical practice. REM-OSA is an important but underrecognized clinical issue in the study of improving the prognosis of cerebral infarction.ObjectiveTo investigate the relationships among REM-OSA and cerebral infarction clinical prognosis.MethodsIn this retrospective cohort study, 318 cerebral infarction patients with OSA (AHI ≥ 5) were enrolled from February 2022 to January 2025 at the Department of Neurology, Affiliated Hospital of Yangzhou University. Participants were stratified into REM-OSA (n = 71) and NREM-OSA (n = 247) groups using stringent criteria (AHIREM/AHINREM ≥ 2, REM duration ≥30 min). Data included polysomnography, neurological assessments (NIHSS, MRS), inflammatory markers (WBC, hs-CRP), and neuroimaging. Statistical analyses comprised logistic regression and Pearson correlation tests.ResultsCompared to NREM-OSA, REM-OSA patients exhibited: (1) Poorer prognosis: Higher 3-month mRS scores (OR = 1.543, p = 0.032), independent of total AHI. (2) Enhanced inflammation: Elevated WBC (7.45 vs. 6.50 × 109/L, p = 0.011) and hs-CRP (3.95vs.1.16 mg/L, p < 0.001), correlating with AHIREM (r = 0.234–0.268, p < 0.001). (3) Unique neuroanatomical vulnerability: Higher basal ganglia infarction prevalence (83.1% vs. 64.8%, p = 0.003; OR = 2.359). (4) Severe REM-specific hypoxia: Lower minimum SpO₂ (81.62% vs. 84.31%, p < 0.001) and prolonged apneas. (5) Sleep architecture disruption: Reduced sleep efficiency and prolonged latency (PSQI: 10.18 vs. 8.52, p = 0.004). (6) Age inversely correlated with REM-OSA severity (r = −0.154, p = 0.020).ConclusionREM-OSA is independently associated with poorer prognosis in cerebral infarction patients. Potential explanatory mechanisms include REM-specific hypoxia, systemic inflammation, and basal ganglia vulnerability.